Cytochrome P450 27C1 Level Dictates Lung Cancer Tumorigenicity and Sensitivity towards Multiple Anticancer Agents and Its Potential Interplay with the IGF-1R/Akt/p53 Signaling Pathway - Mo, Hai-Ying; Wei, Qi-Yao; Zhong, Qiu-Hua; Zhao, Xiao-Yun; Guo, Dan; Han, Jin; Noracharttiyapot, Wachiraporn; Visser, Lydia; van den Berg, Anke; Xu, Yan-Ming; Lau, Andy T. Y. (International journal of molecular sciences, 2022)
Cytochrome P450 enzymes (CYP450s) exert mighty catalytic actions in cellular metabolism and detoxication, which play pivotal roles in cell fate determination. Preliminary data shows differential expression levels of CYP27C1, one of the “orphan P450s” in human lung cancer cell lines. Here, we study the functions of CYP27C1 in lung cancer progression and drug endurance, and explore its potential to be a diagnostic and therapeutic target for lung cancer management. Quantitative real-time PCR and immunoblot assays were conducted to estimate the transcription and protein expression level of CYP27C1 in human lung cancer cell lines, which was relatively higher in A549 and H1975 cells, but was lower in H460 cells. Stable CYP27C1-knockdown A549 and H1975 cell lines were established, in which these cells showed enhancement in cell proliferation, colony formation, and migration. In addition, aberrant IGF-1R/Akt/p53 signal transduction was also detected in stable CYP27C1-knockdown human lung cancer cells, which exhibited greater tolerance towards the treatments of anticancer agents (including vinorelbine, picropodophyllin, pacritinib, and SKLB610). This work, for the first time, reveals that CYP27C1 impacts lung cancer cell development by participating in the regulation of the IGF-1R/Akt/p53 signaling pathway, and the level of CYP27C1 plays indispensable roles in dictating the cellular sensitivity towards multiple anticancer agents.